White matter hyperintensities volume and cognition: A meta-analysis - Guo, Wenjuan; Shi, Jing (Frontiers in Aging Neuroscience, 2022)
Background:Cerebral small vessel disease (CSVD) is prevalent in the elderly and leads to increased risk of cognitive impairment and dementia. The volume of white matter hyperintensities(WMH) increases with age, which affects cognition. Objective: To explore the relationship between WMH volume and cognitive decline in patients with CSVD. Methods: We proceeded to a systematic search of PubMed, Embase, and Web of Science databases from the date of creation to 5th May 2022 to identify all clinical studies of mild cognitive impairment (MCI) or dementia on WMH volume in CSVD. Results: WMH volume increased the risk of MCI in NC patients (six studies, n=2278) RR=1.35; [95%CI: 1.01 - 1.81], I2=72%, P=0.003), with a sample incidence of 15% ( 335/2278), estimated overall population mean 5.6-year incidence rate of MCI (IR=10.25; [95%CI: 5.25 - 15.26]); association of WMH with dementia was (6 studies, n=6330) (RR=1.49 ; [95% CI: 1.21 - 1.84], I2=37%, P=0.16), sample incidence 3% (189/6330), estimated overall population mean 6.2-year dementia incidence rate (IR=5.62; [95%] CI: 2.54 - 8.69]). MCI subjects with WMH had a significantly higher risk of developing dementia (two studies, n=367) than NC subjects (RR=1.01; [95%CI: 0.99 - 1.04], I2=0%, P=0.55) , the incidence of the included sample was 15% (54/367), and the estimated incidence rate in the overall population averaged 4.5 years (IR=12.40; [95%ci: 5.23 - 19.56]). Conclusions: WMH volume was substantially corelated with the risk of cognitive impairment. WMH increases the likelihood of progression to dementia in patients with MCI. Increasing age directly has an impact on the degree of disease progression and morbidity.